Efektivitas Pembelajaran Jigsaw Berbasis Youtube Pada Materi Konsep Statistika Dasar: The Effectiveness of YouTube-Based Jigsaw Learning on Basic Statistics Concepts - Sinar; Kamal Ahmad, Andi; Sardi, Ahmed; Razzaq, Abdul; Ishak (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2025)
This study aims to determine the effectiveness of YouTube-based jigsaw learning in improving student learning outcomes in basic statistics concepts at SMPN 2 Duampanu. Using a quasi-experimental research method with a quasi-experimental design, the study was conducted in the even semester of the 2024/2025 academic year. The results showed a significant increase in scores, with the average pretest score from 52.32 to 74.72 on the posttest, and the average pretest score from 29.40 to 46.04 on the posttest. After implementing YouTube-based jigsaw learning, the learning effectiveness increased by 16.64 points. Statistical analysis using a t-test yielded a t-value of 18.624 for the experiment and 13.396 for the control, > t-table 2.064 (α=0.05), indicating a significant difference in the implementation of YouTube-based jigsaw learning. This proves that YouTube-based jigsaw learning is effective in improving student learning outcomes.